Intervensi Keperawatan Dalam Upaya Peningkatan Keefektifan Pola Nafas Pada Pasien Dengan PPOK - Nur Shodiq, Rahmad, Enita Dewi , S.Kep.,Ns.,M.N (2017)
Background: Chronic Obstructive Pulmonary Disease (COPD) be the most common cause of death in Indonesia every year prevalence is increasing. The estimates that by WHO in 2020 PPOK was ranked the 3rd largest incident was increased because of the air pollution in the form of smoke and the increasing number of people who have the habit of smoking. The tobacco on cigarettes this is what caused the tissue damage and emergence inflammation of the breath It is increasingly long can result in narrowing of the airways and excess sputum production so that the airway is not effective and if not treated immediately it will cause problems ineffective breathing pattern. Objective: Provide an overview improving the ineffective breathing pattern in COPD patients. Methods: This study was performed on patients with COPD, the writer conducted research for two days with a descriptive method by the data related to the patient. Results: After the action for 2x24 hours in COPD patients to seek effectiveness of the breath by teaching techniques of relaxation a deep breath and position semifowler or high fowler and relaxation and granting therapy oxygen with 4 doses liter with nasal kanul, and inhalation.From the first day to the second day of patients still felt suffocation and the permenit respiratory still up the normal.Conclusion: The problem in patients with ineffective breathing pattern is not resolved because of the time of 2x24-hour nursing care for the patient doesn't increase the effectiveness of breathing patterns in accordance with the criteria envisaged outcome.